Mutations in the TBX15‐ADAMTS2 pathway associate with a novel soft palate dysplasia. Issue 12 (30th September 2022) - Zhang, Yuying; Li, Jian; Ji, Yaoting; Cheng, Yibin; Fu, Xiazhou
Abstract: We reported de novo variants in specific exons of the TBX15 and ADAMTS2 genes in a hitherto undescribed class of patients with unique craniofacial developmental defects. The nine unrelated patients represent unilateral soft palate hypoplasia, lost part of the sphenoid bone in the pterygoid process, but the uvula developed completely. Interestingly, these clinical features are contrary to the palate's anterior‐posterior (A‐P) developmental direction. Based on developmental characteristics, we suggested that these cases correspond to a novel craniofacial birth defect different from cleft palate, and we named it soft palate dysplasia (SPD). However, little is known about the molecular mechanism of the ADAMTS2 and TBX15 genes in the regulation of soft palate development. Phylogenetic analysis showed that the sequences around these de novo mutation sites are conserved between species. Through cellular co‐transfections and chromatin immunoprecipitation assays, we demonstrate that TBX15 binds to the promoter regions of the ADAMTS2 gene and activates the promoter activity. Furthermore, we show that TBX15 and ADAMTS2 are colocalization in the posterior palatal mesenchymal cells during soft palate development in E13.5 mice embryos. Based on these data, we propose that the disruption of the TBX15‐ADAMTS2 signaling pathway during embryogenesis leads to a novel SPD.